CL-L1 and CL-K1 Exhibit Widespread Tissue Distribution With High and Co-Localized Expression in Secretory Epithelia and Mucosa - Hansen, Soren W. K.; Aagaard, Josephine B.; Bjerrum, Karen B.; Hejbøl, Eva K.; Nielsen, Ole; Schrøder, Henrik D.; Skjoedt, Karsten; Sørensen, Anna L.; Graversen, Jonas H.; Henriksen, Maiken L. (Frontiers in Immunology, 2018)
Collectin liver 1 (CL-L1, alias collectin 10) and collectin kidney 1 (CL-K1, alias collectin 11) are oligomeric pattern recognition molecules associated with the complement system, and mutations in either of their genes may lead to deficiency and developmental defects. The two collectins are reportedly localized and synthesized in the liver, kidneys and adrenals, and can be found in the circulation as heteromeric complexes (CL-LK), which upon binding to microbial high mannose-like glycoconjugates activates the complement system via the lectin activation pathway. The tissue distribution of homo- vs. heteromeric CL-L1 and –K1 complexes, the mechanism of heteromeric complex formation and in which tissues this occurs, is hitherto incompletely described. We have by immunohistochemistry using monoclonal antibodies addressed the precise cellular localization of the two collectins in the main human tissues. We find that the two collectins have widespread and almost identical tissue distribution with a high expression in epithelial cells in endo- / exocrine secretory tissues and mucosa. There is also accordance between localization of mRNA transcripts and detection of proteins, showing that local synthesis likely is responsible for peripheral localization and eventual formation of the CL-LK complexes. The functional implications of the high expression in endo- / exocrine secretory tissue and mucosa is unknown but might be associated with the activity of MASP-3, which has a similar pattern of expression and is known to potentiate the activity of the alternative complement activation pathway.